Biodegraded polymers as materials for sowing of grain crops seeds - L. S. Shibryaeva; Yu. V. Tertyshnaya; D. D. Pal’Mina; N. S. Levina (Сельскохозяйственные машины и технологии, 2015)
Increase of efficiency of grain production, solution of problems of food security demand search and development of innovative technologies at all stages. One of ways of environmentally friendly production is sowing of seeds on an excipient located in the soil, for example, nonwoven fabric made of eco- decomposable decomposed biodegraded polymer. Biodegraded polymeric materials influence on sowing properties of grain crops seeds and provide realization of their potential productivity. The authors used an electroforming method with chloroform and a dichloroethane application to receive nonwoven fabric from poly-3-hydroxybutyrate (PHB) and its compositions together with synthetic nitrile rubber (PHB-SNR). Polymeric material influences on energy of germination and viability of wheat seeds. Germination index is calculated, heat physical parameters are determined for the polymeric excipient. The major factor influencing seeds germination is a structure of nonwoven fabric. Water diffusion, its supply to seeds and their viability depend on morphological features of polymeric material. Polymer excipient structure influence on speed of development of root system on which, in turn, intensity of destruction of polymer depends. The best indicators of energy of germination and viability of seeds correspond to the greatest value of decrease of melting heat of PHB in mix PHB-SNR. In addition, among the studied samples of PHB-SNR the material received from blend of solvents is most effective. The cause is in feature of its structure favorable for a seed germination.